TINDAK ILOKUSI DALAM PIDATO KEMENANGAN PEMILU BARACK OBAMA TAHUN 2008 - Farhan Aslam, Muhammad; Rudianto, Gaguk (Universitas Putera Batam, 2024)
This study uses a qualitative research approach to examine the illocutionary acts in Barack Obama's 2008 victory speech. The study's data, which focuses on the connection between theory and research, comprises spoken and written words. The researchers employ an observational strategy and note-taking technique to collect data from the speech. The data analysis uses an identification procedure that involves watching and listening to the video and audio to pinpoint the different illocutionary acts that Obama has used. Based on Searle's theory, the researchers categorize the transcriptions and find 21 illocutionary acts, such as directive, commissive, declarative, expressive, and representative. These results demonstrate that Obama's speech contained two directive acts, two commissive acts, five representative acts, six expressive acts, and six declarative acts. This study adds to our knowledge of how theories are revived through qualitative research and offers insightful information on the dynamics of illocutionary acts in speech. The findings provide additional insight into Obama's communication tactics and his rhetorical devices in his victory address. Subsequent investigations in this field may examine the influence and efficacy of illocutionary actions in political dialogue.